Pengembangan Budidaya Tanaman Herbal dan Pemanfaatan Biopori sebagai Upaya Pembangunan Berkelanjutan Pasca COVID-19 di Desa Adat Peliatan, Ubud - Dewi, Ni Wayan Erly Sintya; Cahyawati, Putu Nita; Maha Putra, I Nyoman Gede (Jurnal Pengabmas Masyarakat Sehat, 2025)
Background: The COVID-19 pandemic significantly impacted Peliatan Traditional Village, Ubud, which relied heavily on tourism. The drastic drop in visitors triggered economic hardship and affected community health. Recognizing untapped local potential, this program introduced herbal plant cultivation and biopore technology as sustainable alternatives for improving health and livelihood.Objective: To build community capacity in cultivating herbal plants and managing household organic waste through biopores, thus supporting long-term health, economic resilience, and environmental sustainability.Method: The program involved 30 PKK (Family Welfare Movement) members through education on herbal plants, cultivation techniques, health applications, and hands-on biopore construction. Pre- and post-tests, along with field mentoring, were conducted to assess impact.Result: Participants’ knowledge increased by 35%. All created biopore holes at home, and 20% harvested compost within three months. The initiative also sparked interest in continuing herbal cultivation independently.Conclusion: Education on herbal use and biopore application proved effective in enhancing health awareness and environmental practices. This program represents an initial step toward post-pandemic village resilience based on local resourcesKeyword: COVID-19; community service; herbal plants; health; bio pore